Functional significance of novel variants of the MEF2C gene promoter in congenital ventricular septal defects. Issue 8 (20th June 2022) - Zeng, Zhi‐Hua; Chen, Huan‐Xin; Liu, Xiao‐Cheng; Yang, Qin; He, Guo‐Wei
Abstract: Ventricular septal defect (VSD) is the most common congenital heart disease. Although the coding region of MEF2C is highly relevant to cardiac malformations, the role of MEF2C gene promoter variants in VSD patients has not been genetically investigated. We investigated the role of MEF2C gene promoter variants in 400 Han Chinese subjects (200 patients with isolated and sporadic VSD and 200 healthy controls). The promoter region of the MEF2C gene was sequenced that identified 10 variants. Expression vectors encompassing the variants and the firefly luciferase reporter gene plasmid (pGL3‐basic) were constructed and subsequently transfected into HEK‐293 cells. The luciferase activities were measured by Dual‐luciferase reporter assay system. MEF2C gene promoter transcriptional activity was significantly reduced in 4 of the 10 variants in HEK‐293 cells ( P  < 0.05). In addition, the JASPAR database was used to perform bioinformatics analysis, which showed that these variants disrupt the putative binding sites of transcription factors and affected the expression of MEF2C protein. This study for the first time identified the variants in the promoter of the MEF2C gene in Han Chinese population and revealed the role of these variants in the formation of VSD.